TACTICS OF DRAWING UP COMPETITIONS IN THE SPORT OF SAMBO AND COMBAT SAMBO - Ibadullaev Balkhozha (Proximus Journal Publishing, 2025)
the tactics of Sports Wrestling are regularly developing in accordance with the development of technology, changes in the rules of the competition and the arbitration system. Currently, a tactic in which a standing attack is performed by a wrestler is preferred. In this case, even if he has not organized any attacks that are judged by points, while his opponent is only protected, he will be given an advantage, while the opponent will receive a warning for lethargy.
Keywords: wrestling; competition; sambo